DETERMINING AGRICULTURAL INSURANCE PREMIUMS USING THE BLACK-SCHOLES APPROACH BASED ON LINEAR REGRESSION OF POTATO PRODUCTION AND PRICES - Purwani, Sri; Sutisna, Sarah; Fasa, Rayyan Al Muddatstsir (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Price fluctuations, which often occur in the agricultural sector, cause farmers to experience losses when selling prices are not balanced with production costs. The government is trying to minimize farmers' losses by issuing an agricultural insurance program. One of the problems with agricultural insurance is determining the premium that farmers must pay so as not to disadvantage the insurance company. This paper explores the price of insurance premiums associated with potato cultivation in West Java, Indonesia. In addition, this research analyzes the factors that influence prices by focusing on the relationship between potato production levels and market prices. Therefore, a comprehensive data set of potato production data and associated prices is used. Regression analysis, as a statistical technique, is used to model the relationships. The Black-Scholes method then uses the obtained result to determine insurance premiums. This method is used due to a theoretical framework for pricing options that allows selecting an option's fair price using a structured, defined methodology that has been tried and tested. The premium values that depend on the trigger value are then obtained with a range of prices between IDR 5,687,670 and IDR 18,067,953 for an insured amount of IDR 39,403,000 per contract period. The premium price range allows farmers to choose the right agricultural insurance policy. It also allows insurance companies to determine insurance premiums for potato cultivation.